Стервятник: роман / А. А. Бушков - Бушков Александр Александрович (Русский проект, 1996)
Экземпляры: Шольинская библиотека (20200320) / Инвентарный номер: 8816 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ББК: 84(2Рос=Рус)6